Minimum wage, fringe benefits, overtime payments and the gender wage gap - Kizilca, Kemal (2010)
This paper investigates the impact of an increase in the minimum wage on the gender gap at various levels of employee compansation, namely, base wage, fringe benefits, overtime payments and probability of getting these extra income components. Using the matched employer-employee database for the Portuguese labor market, we explore the 1998 amendment to the MW law that increased the minimum wage applied to employees younger than 18 years of age from 75% to 100% of the full minimum. Estimation results based on a difference-in-difference-differences strategy indicate a widening of the gender gap, caused by redistribution of fringe benefits and overtime payments following the amendment. We discuss three possible sources of redistribution: (i) discrimination, (ii) a change in the skill composition of the working males and females after the increase, and (iii) industrial differences in response to the changes in the wage floor. Estimations support the third channel as the main contributing factor while we cannot eliminate the possibility of the effect of discrimination.